Ultrasonic velocity of water–ethanol–malic acid–lactic acid mixtures during the malolactic fermentation process. (March 2015) - Amer, M.A.; Novoa-Díaz, D.; Puig-Pujol, A.; Capdevila, J.; Chávez, J.A.; Turó, A.; García-Hernández, M.J.; Salazar, J.
Highlights: Ultrasonic velocity correlates significantly with malic and lactic acid concentrations. Ultrasonic velocity could be used to predict the end of the malolactic fermentation process. Velocity of an ultrasonic pulse may be used to monitor the malolactic fermentation process. Abstract: During malolactic fermentation in wines, malic acid is transformed into lactic acid by the action of lactic acid bacteria. This process can be monitored on-line by measuring the velocity of a low intensity ultrasonic wave propagating through the medium. In this work, an experimental study of ultrasonic propagation velocity in laboratory mixtures of water–ethanol–malic acid and lactic acid is presented. A good correlation was found between the ultrasonic velocity and malic and lactic acid concentrations. These results could be used to predict the end-point of the malolactic fermentation process and show the great potential of this ultrasonic technique to determine malic and lactic acid concentrations during the malolactic fermentation process.